Pernikahan dalam hukum adat sasak: perspektif hukum islam pada tradisi kawin culik - ma’ruf, amar (Maliki Interdisciplinary Journal, 2025)
Marriage in the Sasak indigenous community of Lombok Island has a unique characteristic with the ongoing bride-stealing tradition. This tradition is not merely an act of partner theft, but carries a profound meaning within the social structure of the local community. Using qualitative research methods with a literature study approach, through examining various literature sources and references, this study comprehensively explores the Sasak traditional marriage customs. The bride-stealing process involves family negotiations and specific rules. A man "abducts" the woman he likes with the intention of marriage, but not without consideration and consent from both parties. The woman’s family will discuss with the man’s family to determine the relationship’s continuation, followed by various traditional rituals. Interestingly, this practice is not always contrary to Islamic law. The Sasak community, predominantly Muslim, integrates religious values into their traditions. They ensure the bride-stealing process maintains ethics, agreement, and the couple’s dignity. The research aims to analyze the relationship between bride-stealing practices and Islamic legal perspectives, and uncover the complexity of interactions between traditional customs and religious norms in the Sasak community’s marriage practices.